2016
DOI: 10.1101/038687
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Translational plasticity facilitates the accumulation of nonsense genetic variants in the human population

Abstract: Genetic variants that disrupt protein-coding DNA are ubiquitous in the human population, with about 100 such loss-offunction variants per individual. While most loss-of-function variants are rare, a subset have risen to high frequency and occur in a homozygous state in healthy individuals. It is unknown why these common variants are well tolerated, even though some affect essential genes implicated in Mendelian disease. Here, we combine genomic, proteomic, and biochemical data to demonstrate that many common n… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 44 publications
0
20
0
Order By: Relevance
“…As well as novel instances of NMD-escape, it is also possible a subset of these middle exon mutations are in fact undergoing partial (or full) NMD degradation, but remain at sufficiently high transcript abundance to be detected. Translational plasticity has also been described as additional feature impacting NMD efficiency, with a diverse range of mechanisms such as stop codon read through, alternative translation initiation and alternative splicing, being reported as driving NMD escape in the germline setting (29). Furthermore, the highly dysregulated nature of cancer cell transcriptomes may further explain the partial "leakiness" in NMD patterns we observe in this study.…”
Section: Discussionmentioning
confidence: 57%
“…As well as novel instances of NMD-escape, it is also possible a subset of these middle exon mutations are in fact undergoing partial (or full) NMD degradation, but remain at sufficiently high transcript abundance to be detected. Translational plasticity has also been described as additional feature impacting NMD efficiency, with a diverse range of mechanisms such as stop codon read through, alternative translation initiation and alternative splicing, being reported as driving NMD escape in the germline setting (29). Furthermore, the highly dysregulated nature of cancer cell transcriptomes may further explain the partial "leakiness" in NMD patterns we observe in this study.…”
Section: Discussionmentioning
confidence: 57%
“…However, there are several examples of transcripts with start‐proximal nonsense codons that are not subject to NMD due to efficient reinitiation of translation at downstream start codons (Buisson et al, ; Hulsebos et al, ; Paulsen et al, ; Pereira et al, ; Stump et al, ; Stump et al, ; Zhang & Maquat, ), leading to the proposal of a “boundary” within each transcript where reinitiation is efficient (Pereira et al, ). In support of this model, by analyzing common nonsense variants in the human population, we observed a statistically significant enrichment of downstream in‐frame methionine within 50 codons of the nonsense variants (Jagannathan & Bradley, ). Specifically, we found that 57% of rare and 85% of common nonsense variants contained a downstream in‐frame methionine within 50 codons of the variant, compared with only 52% of synonymous variants (Jagannathan & Bradley, ).…”
Section: Gene‐specific Modifiers Of Nmd Efficiencymentioning
confidence: 67%
“…Analyses of publicly available functional genomics data sets to assess the NMD efficiency of a subset of highly common nonsense mutations (i.e. , those that have not been purged by negative selection during evolution) led to the estimation that 52.7% of these common nonsense variants escape NMD (Jagannathan & Bradley, ). Reporter‐based molecular validation further showed that translation reinitiation and stop codon readthrough, among other post‐transcriptional mechanisms, contribute to NMD escape, enabling protein production from the nonsense alleles (Jagannathan & Bradley, ).…”
Section: Gene‐specific Modifiers Of Nmd Efficiencymentioning
confidence: 99%
“…The advent of sequencing studies of large human cohorts has generated a robust pipeline of PTV discovery, which has led to the identification of a number of large-effect associations to diseases or diseaserelated traits (Dewey et al 2016). However, most of the PTVs identified through such studies to date are present in the genomes of apparently healthy individuals (MacArthur et al 2012), suggesting that their phenotypic impact, if any, may not be obvious (Rivas et al 2015;Jagannathan and Bradley 2016).…”
Section: Introductionmentioning
confidence: 99%